2018
DOI: 10.11591/ijece.v8i6.pp5144-5152
|View full text |Cite
|
Sign up to set email alerts
|

Revealing AES Encryption Device Key on 328P Microcontrollers with Differential Power Analysis

Abstract: This research demonstrates the revealing of an advanced encryption standard (AES) encryption device key. The encryption device is applied to an ATMEGA328P microcontroller. The said microcontroller is a device commonly used in internet of things (IoT). We measured power consumption when the encryption process is taking place. The message sent to the encryption device is randomly generated, but the key used has a fixed value. The novelty of this research is the creation of a systematic and optimal circuit in car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Some of the relevant methods against DPA are the use of CAI (cognitive artificial intelligence). We will try to use a masking technique using CAI and information fusion [17,[26][27][28][29] approach.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the relevant methods against DPA are the use of CAI (cognitive artificial intelligence). We will try to use a masking technique using CAI and information fusion [17,[26][27][28][29] approach.…”
Section: Discussionmentioning
confidence: 99%
“…C which is used to block the dc signal and then passed to transistor 1 Q which is used to amplify the voltage. The control unit is anchored by the Arduino UNO ATmega328 microcontroller which many authors including Suresh & Ahmad [23] and others [24,25,26] have employed; and reported its versatility and suitability for a wide range of applications. The program for accepting the filtered analog input signal from the EMF sensor circuit, counting the number of pulses, computing the radiation concentration, display the computed value on the display and log the data to Secure Digital (SD) card is written, compiled, tested and then uploaded to the microcontroller using the Arduino Integrated Development Environment (IDE) software.…”
Section: The Output Is Coupled To Capacitormentioning
confidence: 99%
“…One of them is the advanced encryption standard (AES) has become a popular criterion and is widely used commercially. There are several studies [2]- [14] that use algorithms recommended by the National Institute of Standards and Technology (NIST) as the information security, although several studies have been claimed to break the algorithm [15]- [20].…”
Section: Introductionmentioning
confidence: 99%